Validity of Suspension of Debt Payment Petition Rejected Due to Claim Value: Permohonan Penangguhan Pembayaran Utang Ditolak karena Nilai Klaim - Jonatan, Frangky; Adam, Richard C. (Indonesian Journal of Law and Economics Review, 2025)
General Background: The Suspension of Debt Payment Obligation (PKPU) is an essential legal mechanism within Indonesia’s bankruptcy system that aims to provide debtors the opportunity to restructure their debts and avoid insolvency. Specific Background: However, in practice, several commercial courts have rejected PKPU applications based on the perceived small value of claims, even though Law No. 37 of 2004 on Bankruptcy and PKPU does not stipulate any minimum claim value as a prerequisite. Knowledge Gap: This inconsistency has created legal uncertainty and raised questions about the validity of such rejections in relation to the principles of justice and legal certainty. Aims: This study analyzes the legal basis and validity of PKPU rejections based on claim value and evaluates their conformity with the principles of justice and legal certainty in Indonesian law. Results: The normative legal analysis reveals that rejecting PKPU applications based solely on claim value lacks legal foundation, as it contradicts Article 222 of the Bankruptcy and PKPU Law, which only requires the existence of more than one creditor and a due and payable debt. Novelty: This research provides a comprehensive assessment of the normative gap causing judicial inconsistency in PKPU practices. Implications: The findings emphasize the need for regulatory reform or judicial guidelines to ensure that the PKPU mechanism is applied consistently, fairly, and in support of national legal and economic stability. Highlights:   Legal inconsistency arises from rejecting PKPU based on claim value. Such rejection contradicts Article 222 of the Bankruptcy and PKPU Law. Reform is needed to ensure fairness and consistency in commercial court practice. Keywords: PKPU, Bankruptcy Law, Legal Certainty, Justice, Claim Value